State Failure and International Terrorism: An Analysis of the State of Nigeria as an Incubator of Terror - Essombe, Joel Lambert Lobe (Eastern Mediterranean University EMU, 2017)
The ‘War on Terror’ differs distinctly from the major security challenges that characterized the 20th century, particularly as it is defined by asymmetric warfare, where non-state actors challenge state security. ISIS and Boko Haram are two prominent jihadist groups involved in this conflict. In March 2015, Boko Haram in Nigeria became a branch of ISIS in the West Africa Region. Boko Haram has carried out a number of attacks in Central and West region of Africa against Nigeria, Chad, Niger and Cameroon, making it an international agent. Some queries are raised about the presence and the lack of control by the competent state authorities. Thus Nigeria is considered by some scholars as an incubator of global terror. This claim is also challenged by those who argue there is no clear link between failed or failing states and international terrorism. The aim of this research is to find the relationship between failed or failing states and transnational terrorism. This study will contribute to the scholarly debate on international security. Thus, the topic aims to enrich the discussion on failed states and terrorism in international relations. The findings would seek to contribute to practitioner knowledge regarding potential failed state governments and the dangers these present to the international community as a whole. Keywords: Failed states, Failing states, International terrorism, Nigeria

ÖZ: ‘Teröre Karşı Savaş’, 20. yüzyıla damgasını vuran başlıca güvenlik zorluklarından, özellikle de devlet dışı aktörlerin devlet güvenliğine meydan okuduğu asimetrik savaş ile tanımlandığı gibi belirgin biçimde farklılık göstermektedir. DEAŞ ve Boko Haram, bu çatışmada yer alan önde gelen iki cihat grubudur. Mart 2015’te Nijerya’daki Boko Haram, Batı Afrika Bölgesi’nde DEAŞ’ın şubesi hükmünde olmuştur. Boko Haram, Afrika’nın Orta ve Batı bölgesinde Nijerya, Çad, Nijer ve Kamerun’a karşı bir dizi saldırı düzenlemiş ve cihatçı terörün uluslararası bir temsilcisi haline gelmiştir. Yetkili devlet makamlarının varlıkları ve kontrol eksiklikleri hakkında bazı sorular/sorunlar gündeme getirilmiştir. Böylece Nijerya, bazı araştırmacılar/akademisyenler tarafından küresel teröre karşı bir kuluçka kaynağı olarak düşünülür. Bu iddia, başarısız veya başaramayan devletler ile uluslararası terörizm arasında net bir bağlantı olmadığını iddia edenler tarafından da gündeme getirilmektedir. Bu araştırmanın amacı, başarısız veya başaramayan devletler ile ulus aşırı/sınır aşırı terörizm arasındaki ilişkiyi bulmaktır. Bu çalışma, uluslararası güvenlik konusundaki akademik tartışmalara katkıda bulunacaktır. Böylece, konu uluslararası ilişkilerde başarısız devletler ve terörizm üzerine tartışmayı zenginleştirmeyi amaçlamaktadır. Elde edilen bulgular, potansiyel başarısız devlet hükümetlerine münhasır uygulayıcı bilgiye katkıda bulunmak ve bu müşahhas tehditlerin bir bütün olarak uluslararası topluma sunulması niyetindedir. Anahtar Kelimeler: Başarısız durum, Başarısız devlet, Uluslararası terörizm, Nijerya.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2017. Supervisor: Assist. Prof. Dr. John Turner.
Keywords: Political Science and International Relations; International Terrorism; Terrorism-Nigeria; Failed states; Failing states; International terrorism; Nigeria